Optimizing hypertension care in the real world: a physician survey on telmisartan‑based combination therapy - Mohod, Bhagyashree Arvind; Mayabhate, Mayur Madhav; Sharma, Akhilesh Dayanand; Marda, Uma Laxmikant (International Journal of Research in Medical Sciences, 2026)
Background: Hypertension is a leading cause of global cardiovascular morbidity and mortality and most patients require combination therapy to achieve recommended blood pressure targets and reduce cardiovascular risk. Methods: This cross-sectional, questionnaire-based survey was conducted among 98 physicians attending a scientific meeting organized by the Cardiological society of India (CSI). The survey evaluated real-world hypertension management, including BP targets, use of combination therapy, preferred drug combinations and factors influencing telmisartan selection. Results: Most physicians reported frequent use of combination therapy at the time of treatment initiation, with 46% indicating its use in 20-40% of patients and 38% in 40-60% of patients. Blood pressure targets varied, with nearly half of respondents (48%) aiming for <130/80 mm Hg, while 30% targeted <140/90 mm Hg. Telmisartan plus amlodipine emerged as the most preferred first‑line combination (48%), followed by telmisartan plus chlorthalidone (31%). The telmisartan–amlodipine combination was commonly selected for patients with uncontrolled blood pressure (44%) and those presenting with stage 2 hypertension (41%). Triple therapy with telmisartan, cilnidipine, and chlorthalidone was predominantly reserved for resistant hypertension (57%). Regression of left ventricular hypertrophy (31%) and the presence of microalbuminuria (29%) were key factors influencing preference for telmisartan. Conclusions: The survey highlights a growing preference among clinicians for early combination therapy, intensive BP targets and therapies providing sustained 24-hour BP control. Telmisartan-based combinations were widely preferred, reflecting their complementary mechanisms and cardio-renal protective benefits. These findings suggest increasing adoption of guideline-directed strategies in real-world hypertension management.